2002
DOI: 10.1111/j.0014-3820.2002.tb01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Affect the Magnitude of Inbreeding Depression in Survival of Darwin's Finches

Abstract: Abstract. Understanding the fitness consequences of inbreeding (inbreeding depression) is of importance to evolutionary and conservation biology. There is ample evidence for inbreeding depression in captivity, and data from wild populations are accumulating. However, we still lack a good quantitative understanding of inbreeding depression and what influences its magnitude in natural populations. Specifically, the relationship between the magnitude of inbreeding depression and environmental severity is unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
113
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(116 citation statements)
references
References 73 publications
3
113
0
Order By: Relevance
“…This result is in agreement with that reported by Keller et al. (2002) in song sparrows ( Melospiza melodia ) as they found that inbred males produced fewer offspring in cooler years, but their productivity was similar in comparison with their outbred contemporaries after warm springs. Further, we have previously found that immigrant females, which represent the bulk of gene flow in blue tits, tend to be more heterozygous than residents in our study populations (García‐Navas, Ferrer, Sanz et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in agreement with that reported by Keller et al. (2002) in song sparrows ( Melospiza melodia ) as they found that inbred males produced fewer offspring in cooler years, but their productivity was similar in comparison with their outbred contemporaries after warm springs. Further, we have previously found that immigrant females, which represent the bulk of gene flow in blue tits, tend to be more heterozygous than residents in our study populations (García‐Navas, Ferrer, Sanz et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we quantified the relationship between heterozygosity and fitness along an environmental continuum, comprising harsh (wet–cool) and benign (dry–warm) years. Our results suggest that interannual variability in environmental harshness can affect the magnitude of HFC (Forcada & Hoffman, 2014; Keller et al., 2002). Among the studied environmental parameters, only accumulated rainfall was associated with selection differentials for heterozygosity (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inbreeding depression in the wild was largely believed to be non-existent for a long time, but has recently been repeatedly verified (reviewed in Frankham 1995Frankham , 2005, for example, in adder snakes Vipera berus (Madsen et al 1999) and Darwin's finches Geospiza sp. (Keller et al 2002), in the latter case only under nutritional constraints.…”
Section: Introductionmentioning
confidence: 97%
“…Among the studies reviewed by Armbruster & Reed [9] only 9 of 34 measured inbreeding depression under field conditions and only 4 measured natural temporal variation in levels of inbreeding depression in wild populations [18 -21]. For example, in populations of Darwin's finches inbreeding depression for adult and juvenile survival was found to be strongly influenced by food availability and the presence of competitors [19], while in song sparrows periods of rain were shown to significantly increase inbreeding depression for hatching success [20]. However, none of the studies were able to quantify the level of stress.…”
Section: Introductionmentioning
confidence: 99%